Pediatric Sedation: A Global Challenge - David Gozal; Keira P. Mason (International Journal of Pediatrics)
Pediatric sedation is a challenge which spans all continents and has grown to encompass specialties outside of anesthesia, radiology and emergency medicine. All sedatives are not universally available and local and national regulations often limit the sedation practice to specific agents and those with specific credentials. Some specialties have established certification and credentials for sedation delivery whereas most have not. Some of the relevant sedation guidelines and recommendations of specialty organizations worldwide will be explored. The challenge facing sedation care providers moving forward in the 21st century will be to determine how to apply the local, regional and national guidelines to the individual sedation practices. A greater challenge, perhaps impossible, will be to determine whether the sedation community can come together worldwide to develop standards, guidelines and recommendations for safe sedation practice.